Balancing the scales: Custody deprivation and fostering in Iceland. (July 2019) - Sigurjónsdóttir, Hanna Björg; Harwick, Robin; Rice, James
In Iceland, disability receives disproportionate attention in custody deprivation investigations, while the long-term outcomes for children in fostering receive scant attention. Building on discourse analyses of custody deprivation cases, we call for greater understanding of how disability intersects with parenting and the need for an improved support system.